Restorative Justice in Resolving Criminal Acts by Children - Salsabilla, Salisah (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
This research explores the implementation of Restorative Justice in resolving criminal acts committed by children within the Indonesian legal system. Restorative Justice offers an alternative approach to conventional criminal justice by emphasizing reconciliation between the offender, victim, and society through mediation and dialogue. The study adopts a normative juridical method, analyzing relevant laws, literature, and expert opinions, with a focus on the application of diversion as regulated by Law No. 11 of 2012 on the Juvenile Criminal Justice System. The findings reveal that Restorative Justice provides significant benefits, including minimizing the psychological impact of formal legal processes on children, promoting victim participation, and strengthening social cohesion. However, challenges remain in its implementation, such as limited understanding among law enforcement officials and inadequate resources. Strengthening training, public awareness, and inter-agency cooperation are essential to optimize Restorative Justice practices for child offenders in Indonesia.